Fine modulation of the respiratory syncytial virus M2-1 protein quaternary structure by reversible zinc removal from its Cys(3)-His(1) motif - Esperante, Sebastian (2013)
Human respiratory syncytial virus (hRSV) is a worldwide distributed pathogen that causes respiratory disease mostly in infants and the elderly. The M2-1 protein of hRSV functions as a transcription antiterminator and partakes in virus particle budding. It is present only in Pneumovirinae, namely, Pneumovirus (RSV) and Metapneumovirus, making it an interesting target for specific antivirals. hRSV M2-1 is a tight tetramer bearing a Cys3-His1 zinc-binding motif, present in Ebola VP30 protein and some eukaryotic proteins, whose integrity was shown to be essential for protein function but without a biochemical mechanistic basis. We showed that removal of the zinc atom causes dissociation to a monomeric apo-M2-1 species. Surprisingly, the secondary structure and stability of the apo-monomer is indistinguishable from that of the M2-1 tetramer. Dissociation reported by a highly sensitive tryptophan residue is much increased at pH 5.0 compared to pH 7.0, suggesting a histidine protonation cooperating in zinc removal. The monomeric apo form binds RNA at least as well as the tetramer, and this interaction is outcompeted by the phosphoprotein P, the RNA polymerase cofactor. The role of zinc goes beyond stabilization of local structure, finely tuning dissociation to a fully folded and binding competent monomer. Removal of zinc is equivalent to the disruption of the motif by mutation, only that the former is potentially reversible in the cellular context. Thus, this process could be triggered by a natural chelator such as glutathione or thioneins, where reversibility strongly suggests a modulatory role in the participation of M2-1 in the assembly of the polymerase complex or in virion budding.